Lifestyle-exposure theory as a framework to analyze victimization of people experiencing homelessness - Puente Guerrero, Patricia (Deviant behavior, 2023)
Segmentation analysis and logistic regression were used to test the probabilistic connection between exposure to high-risk situations and victimization events, as posited by Lifestyle-exposure theory, in a sample of homeless people. The results support the hypothesis put forward. First, those who had engaged in risky behaviors had suffered victimization events to a greater extent. Second, this was particularly true for participants who had done so more frequently or had engaged in a wider range of such behaviors. The highest risk profile included those who had been arrested on several occasions and also reported having used drugs during the previous month or, otherwise, had served a sentence different from prison in the past. Implications of these findings are discussed considering that homeless people’s engagement in risky behaviors, as well as, in general, their greater degree of exposure to situations in which risk of victimization is high, often stem from the situation they are going through. A major conclusion is that any effort to eradicate violence against homeless people should contemplate strategies for combating homelessness itself.